Feminist Collections, v.25, no.2 (winter 2004) - (:unkn) unknown (My University, 2004)
Subtitle: A Quarterly of Women's Studies Resources. 37p.
Contents: FROM THE EDITOR. BOOK REVIEW: Watch Out! Alison Bechdel’s Comics as Cultural Commentary, by Briana Smith. FEMINIST VISIONS: Practicing Art: A Review of Three Videos, by Helen Klebesadel. FINDING FUNDING FOR WOMEN: Web and Non-Web Resources, by Elizabeth Breed. E-SOURCES ON WOMEN & GENDER: By JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Mary Pfotenhauer, Jessica Poland, & Phyllis Holman Weisbard. REBEL SONG: Feminist Zines from the (Southern) Third Wave, by M.L. Fraser. PERIODICAL NOTES: Special Issues, by Stephanie Rytilahti. ITEMS OF NOTE: By Mary Pfotenhauer. BOOKS/AV RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Alison Bechdel; Feminist Artist Videos; Funding Sources; Zines; comics; Grants; Financial Aid; E-Sources; E-Sources